ANALISIS YURIDIS PERANAN NOTARIS DALAM PRAKTEK GADAI SAHAM PERSEROAN TERBATAS PADA BANK - VINA VERAWATY PASARIBU (PREMISE LAW JURNAL, 2014)
ABSTRACT Article 60 paragraph (2) of Law No.40/2007 on Limited Liability Company says that “share can be collaterized through mortgage or fiducial guarannte as long as it is not specified in the statutes”. Further, Article 60 paragraph (3) of Law No.40/2007 on Limited Liability Company says that mortgage of share or fiducial guaranteee for the share which has been registered in accordance with the regulation of legislation needs to be recorded in the list of share holders and special list. Then, Article 60 paragraph (4) of Law No.40/2007 on Limited Liability Company says that right to vote related to the share collaterized through mortgage or fidfucial guarantee remains in the hands of share holders. Based on the legal provisions stated in the Article 60 paragraphs (2),(3), and (4) of Law No.40/2007 on Limited Liability Company, share mortgage can be done as an additional collateral agreement following the main collateral agreement. The execution of mortgaged shares can also be implemented through mediation/ judge’s permission and through court decision asked or applied by the recepient of mortgaged shares. Keywords: Role of Notary, Share Mortgage, Limited Liability Company, Bank